Creativity in marketing communication to overcome barriers to organic produce purchases: The case of a developing nation. (1st January 2020) - Mkhize, Sandile; Ellis, Debbie
Abstract: The change from conventional to organic foods has been found to have benefits for environmental sustainability and for consumers' health. Although a market for organic fresh produce has been found to exist in South Africa, consumption levels are low and there is incomplete understanding of the barriers to organic consumption. In this qualitative research interviews were conducted with participants who were aware of organic products but were not regular consumers of organic products. Snowball sampling was used to recruit participants to the study to better understand barriers to organic purchases. Qualitative data obtained from interviews was transcribed and thematic analysis conducted. Generally, participants appeared to be concerned about the environment, however, their concern for the environment does not lead to organic consumption. Furthermore, participants had positive attitudes toward organic products, are not influenced by friends and family but are deterred by issues such as price, availability and labelling of organic products. The recommendations include initiatives that will assist marketers with communicating organic benefits to consumers thereby explaining the reasons for higher prices and leading to consumer trust. Creative communication strategies present an opportunity to overcome barriers to consumption.